An Impact Assessment Study of MGNREGA in Bihar - Mukesh Kumar Mishra (ResearchGate, 2024)
India's plan to end rural poverty through inclusive development, asset creation, and employment creation includes MGNREGA as a key element. Its effectiveness hinges on resolving implementation issues and balancing them with more comprehensive programs meant to promote holistic rural development. By ensuring a minimal level of employment, it also plays a critical role in fostering livelihood security in rural India, which in turn helps to alleviate poverty and promote overall rural development. The aim of the paper is to assess the impact of MGNREGA, and the study is confined to Dhabauli West, Bishanpur and Patarghat Gram Panchayat of Patarghat, Saharsa district in Bihar state. The research is based on an empirical study of both primary and secondary data. The main findings of the study are that villagers are taking advantage of the scheme and enhancement of socio-economic status.
Keywords: 330; MANREGA; Bihar; Inclusive Development; Employment; Poverty